Character Strengths Profiles in Medical Professionals and Their Impact on Well-Being - Huber, Alexandra; Strecker, Cornelia; Kachel, Timo; Höge, Thomas; Höfer, Stefan (Frontiers in Psychology, 2020)
Character strengths profiles in the specific setting of medical professionals are widely unchartered territory. This paper focused on an overview of character strengths profiles of medical professionals (medical students and physicians) based on literature research and available empirical data illustrating their impact on well-being and work engagement. A literature research was conducted and the majority of peer-reviewed considered articles dealt with theoretical or conceptually driven ‘virtues’ associated with medical specialties or questions of ethics in patient care (e.g., professionalism, or what makes a good physician). The virtues of compassion, courage, altruism, and benevolence were described most often. Only a limited number of papers addressed character strengths of medical students or physicians according to the VIA-classification. Those articles showed that the VIA-character strengths fairness, honesty, kindness, and teamwork were considered most often by respondents to be particularly important for the medical profession. Available cross-sectional (time span: six years) and longitudinal (time span: three years) data regarding VIA-character strengths profiles of medical professionals were analyzed (N = 584 medical students, 274 physicians). These profiles were quite homogenous among both groups. The character strengths fairness, honesty, judgment, kindness, and love had the highest means in both samples. Noteworthy differences appeared when comparing medical specialties, in particular concerning general surgeons and psychiatrists, with the former reporting clearly higher levels of e.g., honesty (d = 1.02) or prudence (d = 1.19). Long-term results revealed significant positive effects of character strengths on well-being and work engagement (e.g., perseverance on physicians’ work engagement) but also significant negative effects (e.g., appreciation of beauty and excellence on students’ well-being). Further, hope was significantly associated both positively with physicians’ well-being and negatively with students’ work engagement, possibly indicating specific issues concerning medical education or hospital working conditions. According to the modern-day physician’s pledge, medical professionals should pay attention to their own well-being and health. Therefore, promoting self-awareness and character building among medical professionals could be a beneficial strategy.